"Cultivating Ways of Thinking": The Developmental Teaching Perspective in Academic Advising. Issue 1 (January 2016) - McGill, Craig M.
Abstract: Although academic advising is recognized as an important piece in college student retention, the complexity of the activity and its pedagogical potential continues to be overlooked by institutional stakeholders and advisors themselves. Many outside the field do not fully recognize its purpose and potential, but increasingly advising is seen as a teaching and learning endeavor. Despite the clear connection between teaching and advising, many advisors might still see their roles as course recommenders rather than teachers who are fundamental constituents of an institution's teaching mission. Developmental academic advising is an approach concerned the "whole student, " challenging students to develop in academic, career, and personal vectors. Developmental advising positions the activity to be a truly educative endeavor. In this paper, I discuss eight aspects of developmental advising/advisors identified through reflecting upon of my practice.